2016
DOI: 10.1016/j.ijcard.2016.03.035
|View full text |Cite
|
Sign up to set email alerts
|

ePLAR — The echocardiographic Pulmonary to Left Atrial Ratio — A novel non-invasive parameter to differentiate pre-capillary and post-capillary pulmonary hypertension

Abstract: ePLAR is a simple echocardiographic parameter which can accurately differentiate the smaller subset of patients with pre-capillary pulmonary hypertension from the more common post-capillary aetiology. The use of this easily obtained echocardiographic parameter has the potential to enhance non-invasive triage of patients for specific pulmonary vasodilator therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 47 publications
0
43
0
Order By: Relevance
“… Measure of the transpulmonary gradient (precapillary vs. postcapillary pulmonary hypertension): ePLAR is calculated from the maximum tricuspid regurgitation continuous wave Doppler velocity (m/s) divided by the transmitral E wave: septal mitral annular Doppler tissue imaging e′‐wave ratio (TRV max /E:e′) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Measure of the transpulmonary gradient (precapillary vs. postcapillary pulmonary hypertension): ePLAR is calculated from the maximum tricuspid regurgitation continuous wave Doppler velocity (m/s) divided by the transmitral E wave: septal mitral annular Doppler tissue imaging e′‐wave ratio (TRV max /E:e′) …”
Section: Resultsmentioning
confidence: 99%
“…During pneumonia, there was predominantly an increase in PASP without significant change in left ventricular filling pressures. Scalia et al have shown a significantly greater ePLAR in patients with precapillary pulmonary hypertension than in those with postcapillary pulmonary hypertension …”
Section: Discussionmentioning
confidence: 96%
“…Increased scrutiny of the various echocardiography measurements will lead to increased accuracy of noninvasive measurements. As this improves and with the advent of new echo parameters like ePLAR, the necessity for regular right heart catheterization may be reduced …”
Section: Discussionmentioning
confidence: 99%
“…Transthoracic echocardiography (TTE) has been the primary method of noninvasive assessment of right heart pressures over the last 30 years . As new therapies for the treatment of pulmonary hypertension emerge and with new echocardiography parameters like the echocardiographic pulmonary to left atrial ratio (ePLAR) available for assessment of pulmonary hypertension (PH), there is increasing scrutiny of the accuracy of Doppler ultrasound in estimating right ventricular systolic pressure (RVSP). It is widely accepted that there is a good correlation between invasive pulmonary artery systolic pressure (PASP) and echocardiography estimation of RVSP using tricuspid regurgitant velocity (TRV max ) .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to evaluate precapillary PAH, the echocardiographic pulmonary to left atrial ratio (ePLAR) was calculated as follows: peak tricuspid regurgitation velocity (m/s) divided by the ratio of early transmitral velocity to tissue Doppler mitral annular early diastolic velocity (E/e 0 ratio). 10…”
Section: Echocardiographymentioning
confidence: 99%